The Jewish Middle Ages - Bakhos, Carol; Langer, Gerhard (The Bible and women, 2023)
For many, the Middle Ages in general evokes a sense of the sinister and brings to mind a world of fear, superstition, and religious fanaticism. For Jews it was a period marked by persecutions, pogroms, and expulsions. Yet at the same time, the Middle Ages was also a time of lively cultural exchange and heightened creativity for Jews. In The Jewish Middle Ages, contributors explore the ways in which the stories of biblical women including, Eve, Sarah, Hagar, Rebekah, Zipporah, Ruth, Esther, and Judith, make their way into the rich tapestry of medieval Jewish literature, mystical texts, and art, particularly in works emanating from Ashkenazic circles. Contributors include Carol Bakhos, Judith R. Baskin, Elisheva Baumgarten, Dagmar Börner-Klein, Constanza Cordoni, Rachel Elior, Meret Gutmann-Grün, Robert A. Harris, Yuval Katz-Wilfing, Sheila Tuller Keiter, Katrin Kogman-Appel, Gerhard Langer, Aurora Salvatierra Ossorio, and Felicia Waldman. These essays give us a glimpse into the role women played and the authority they assumed in medieval Jewish culture beyond the rabbinic centers of Palestine and Babylonia--